ELEKTRON PULLAR VA UNING QULAYLIKLARI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides information about how electronic money was created and its history, as well as what laws and decisions were adopted and what indicators were recorded over the years.